1985
DOI: 10.1161/01.res.56.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of ventricular arrhythmias elicited by ischemia followed by reperfusion. Studies on isolated canine ventricular tissues.

Abstract: The purpose of this study was to develop an isolated tissue model in which arrhythmic activity could be generated in response to conditions encountered in ischemia followed by reperfusion, and in which intracellular recordings could be used to identify and study arrhythmogenic mechanisms. Isolated canine Purkinje fiber-papillary muscle preparations were superfused with modified Tyrode's solutions. Tissues were exposed to conditions observed in ischemia (hypoxia, acidosis, elevated lactate, zero substrate for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(87 citation statements)
references
References 42 publications
6
80
1
Order By: Relevance
“…The superfusate was then changed to one of abnormal composition, simulating the extracellular fluid of ischaemic muscle, as suggested by Ferrier et al (1985). This fluid contained KCl 7mM and sodium lactate 20 mm, was made up without added glucose, and had a pH of 6.4 produced by reduction of the NaHCO3 concentration to 4mM.…”
Section: Simulated Ischaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The superfusate was then changed to one of abnormal composition, simulating the extracellular fluid of ischaemic muscle, as suggested by Ferrier et al (1985). This fluid contained KCl 7mM and sodium lactate 20 mm, was made up without added glucose, and had a pH of 6.4 produced by reduction of the NaHCO3 concentration to 4mM.…”
Section: Simulated Ischaemiamentioning
confidence: 99%
“…In SI of cardiac muscle in vitro, conduction velocity (CV) of action potentials is reduced, as are both action potential duration and refractory periods (Ferrier et al, 1985;Northover, 1987). These changes probably constitute the electrical basis for at least some of the disturbances of rhythm that characterize myocardial ischaemia in vivo (Northover, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…at 10 min after the onset of ischaemia). However, since reperfusion causes rapid washout of K+ from the extracellular space (Watanabe et al, 1988) and rapid hyperpolarization (Ferrier et al, 1985) then QT values during early reperfusion (which we cannot measure) may be better reflected by equivalent values during early ischaemia (e.g. after 10 min at which time extracellular K+ is less elevated ;Hirche et al, 1980) than values at 29 min (when K+ values reach as much as 30 mM; Hirche et al, 1980).…”
Section: Control Uk66914mentioning
confidence: 87%
“…In contrast, the latter was caused by increased ventricular automaticity and associated with a low frequency of Vfib. 26 On the other hand, Ferrier et al 5 reported that in isolated tissue preparation, DADs and triggered rhythms occurred during conditions that mimicked reperfusion after a 40-minute ischemic episode. Subsequently, this mechanism has also attracted considerable attention as the underlying mechanism of reperfusion arrhythmias, although this has not been demonstrated clinically in patients who have undergone reperfusion therapy because of AMI.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 99%
“…4,16,26 In contrast, VT is caused by either reentrant or nonreentrant mechanisms and in some cases by triggered activity as a result of DAD. 4,5 However, the reperfusion arrhythmias found in the clinical setting may differ from those observed in experimental models, because factors such as lesion location, collateral flow grade, time to reperfusion, and coronary flow volume can vary. Even among clinical studies, varied incidence of reperfusion arrhythmias has been demonstrated.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 99%